Intervention Model for Amelioration of the Disruptive Behaviors in Children with ADHD. A Case Study - Salceanu, Claudia; Ivașcu, Felicia (Technium Social Sciences Journal, 2022)
The ADHD is a chronic physiological disorder that interferes with a person's ability to regulate and inhibit their behavior and to support attention in solving tasks, in ways appropriate to their level of development. The current study aims to present a recuperative program that we conducted with a five year old boy. The initial and final assessment were conducted with developmental screenings from PEDa Platform (Cognitrom, Cluj-Napoca) and we also used the CBQ Questionnaire. We analyzed the current situation of the subject, applied the recuperative activities and compared the results with the final assessment. We discovered some differences in the scores, although not as large as we would expect. The results are discussed in the context of the family environment and of the importance of the developmental milestones that children with ADHD have to attain.